Acoustic and viscometric studies of ternary liquid mixtures of aqueous sodium methyl p-hydroxybenzoate with polyethylene glycols at 250C. (May 2020) - Thakur, Ashima; Juglan, K.C.; Kumar, Harsh
Abstract: The various ultrasonic parameters like acoustic impedance, adiabatic compressibility, intermolecular free length, relaxation time, relative association, attenuation and Gibb's free energy of polyethylene glycols with molecular weight 200 and 600 in aqueous sodium methyl para-hydroxybenzoate is evaluated at 25 0 C from the density, speed of sound and viscosity. Jone-Dole's equation has been employed to analyze the experimental results of viscosity. The existence of interaction among the fragments of ternary liquid mixtures has been determined from viscosity coefficients. The polyethylene glycols act as the structure builder in water. The viscosity coefficient B surges with escalation in molecular mass of polyethylene glycols. The structure builder property of polyethylene glycols follows the order PEG-600 > PEG-200.